The Reproductive biology of Erica pudens - Dignon, Niki (Department of Biological Sciences, 2015)
Erica is the largest genus in the Cape Florisitic Region (CFR) boasting a diverse range of floral morphology and pollination systems. Even though it is such a diverse genus, there is minimal research examining the pollination biology of specific species. This research inspects the pollination biology of Erica pudens. To do this we carried out pollinator exclusions, hand pollination experiments, rodent trapping, camera observations and pollen/ovule counts. This research also establishes whether E. pudens is another example of convergent evolution in Erica by establishing its phylogenetic position. E. pudens possesses floral characteristics that are consistent with the rodent-pollination syndrome. These characteristics include tightly-packed, pendulous inflorescences with a prostrate habit, found close to the floor, with a dull flower colour and winter flowering times. This research also found that E. pudens offers a high volume of nectar per floral head (up to 20.9Î¼l) with a comparably high sugar concentration (23.7%). Even though these characteristics suggested rodent-pollination, there was no other evidence that conclusively demonstrated this. Only three rodents were captured, and few pollen tetrads were found in the faeces of the two Rhabdomys pumilio individuals (average of 13 and 1 respectively). There was very little footage captured of rodent activity around E. pudens flowers and none to demonstrate the foraging activities of a potential pollinator. The exclusion of pollinators showed no significant difference in swollen ovule dimensions between bagged flowers and caged flowers. Breeding experiments showed no significant difference between self-pollinated flowers and cross-pollinated flowers. These results suggested no need for a pollinator and the ability of E. pudens to undergo self-pollination. This could be an example of pollinator failure (due to small rodent populations) and the consequent evolution of self-pollination. The phylogenetic studies showed that E. pudens was another example of convergent evolution within Erica.